Development of a method for isolating carotenoids from tomato mass (International Journal of Biology and Chemistry, 2018)
The article discusses a method for isolating carotenoids from tomato paste unsuitable for use in the food industry. It is known that the content of lycopene in tomatoes of various varieties varies in wide ranges, therefore, to obtain a natural preparation of lycopene, it is necessary to select varieties of tomatoes with its high content. Carotenoids are practically the only and relatively affordable source of vitamin A (retinol), and in most cases, their use does not lead to an overdose of this vitamin. It should also be noted that despite the wide range of biological activity of carotenoids and the fact that the substances of this class are non-toxic, readily available and relatively cheap to obtain, only some foreign medicines based on β-carotene are known (usually in combination with vitamins E and C). However, the development of effective means of drug therapy based on this class of compounds requires a detailed comparative study of their biological activity. Currently, carotenoids such as beta-carotene, lycopene, lutein, and astaxanthin have been widely used as biologically active components. This is due to their antioxidant, immunostimulating, anticarcinogenic and other features. The difficulty of isolating carotenoids is that representatives of this class in the plant world are in the form of associates with various biopolymers. One of the important organic compounds of natural origin is a fat-soluble carotenoid – lycopene. It is a tetraterpene, which consists of eight isoprene units, a valuable food coloring and antioxidant. The special value of lycopene is that, being a strong antioxidant, it effectively helps to reduce the concentration of harmful cholesterol in the blood. Taking lycopene, a person enhances his defense related to the violation of acid-base balance in the body, as well as problems of the prostate and potency. Also, according to several studies, lycopene can slow down the aging process. We have developed a method for the isolation of lycopene and β-carotene from the tomato mass, selected the optimal extraction conditions. Of all the tested solvents, the optimal extractants were: methyl chloride, acetone and chloroform, since the carotenoids are most completely extracted in these solvents. The extraction process, the amount of carotenoids from the tomato mass was carried out by hot maceration. Also, methods of standardization of isolated substances have been developed; UVspectrometry has been selected as the most convenient and sufficiently accurate method.